Influence of Biological, Social and Psychological Factors on Abnormal Eating Attitudes among Female University Students in Brazil (Journal of Health, Population and Nutrition, 2010)
The objective of the study was to estimate abnormal eating attitudes influenced by associated factors among female students of the Universidade Federal de Santa Catarina, Florianópolis, southern Brazil. Abnormal eating attitudes were investigated using the eating attitudes test (EAT-26), according to the presence (EAT+) and absence (EAT-) of symptoms in a sample of 220 students. The body-image was assessed by the bodyshape questionnaire (BSQ-34). Body mass index, body-fat percentage, waist-circumference, food intake (24-hour food recall), and socioeconomic characteristics (monthly household income, monthly per-capita income, and parental schooling) were also investigated. Statistical associations were tested by multivariate Poisson regression analysis. The prevalence of EAT+ and dissatisfaction with the body-image were 8.3% [confidence interval (CI) 95% 4.6-12.0] and 20.0% (CI 95% 14.7-25.3) respectively. Dissatisfaction with the body-image maintained its independent association with abnormal eating attitudes, indicating symptoms of anorexia nervosa. The results of this work highlight the importance of the planning of nutrition-education programmes in universities, aiming at assisting in the choices of food that comprise a healthful diet in a period of life of so many changes and decisions. Key words: Anorexia nervosa; Attitudes; Body-image; Calorie intake; Cross-sectional studies; Eating disorders; Exploratory studies; Nutritional status; Brazil DOI: 10.3329/jhpn.v28i2.4889 J Health Popul Nutr 2010 Apr; 28(2): 174-181